(untitled) (Quinto Sol, 2013)
This article is a synthesis of the first part of a book in preparation that studies the initial stage of the Hispanic occupation of the River Plate area. In it, as in the rest of America, the arrival of the invader deeply affected all the manifestations of life existing in the territory. Local ecosystems were significantly altered and aboriginal populations were subjected to a violent demographic pressure, to a crucial modification of their social structures and to a strong reconfiguration of their territorial relations. These changes are discussed in the pages that follow.